The effects of work task difficulty on health information searching behaviour - Taheri, Abolfazl; Yousefianzadeh, Omid; Saeedizadeh, Marzieh (Malaysian Journal of Library and Information Science, 2023)
Information needs and information seeking processes depend on contextual factors. Identifying and paying attention to contextual factors such as work tasks can be helpful for personalization of information retrieval. This study aimed to determine the relationship between work task difficulty and interactive health information searching behaviour (HISB). The study was performed through an analysis of transaction logs to identify relation between the work task difficulty and HISB of postgraduate student health ambassadors (PSHB). Thirty participants were purposefully sampled and invited to complete four simulated work tasks. User perception of work task difficulty, satisfaction, and success of search process were measured using questionnaires. A total of 120 log files were analysed. The results showed that with increasing tasks difficulty, PSHB see more results pages, review more information items and finally save more documents. Also, with increasing difficulty, PSHB enter more and longer queries in information retrieval systems and, in addition to changing the query more, they use more keywords and longer queries to search. As the task difficulty increases, the rate of satisfaction and success, as well as the navigational speed decrease. Understanding how work task attributes affect HISB can be effective for designers of interactive information retrieval systems, and developers of personalized health information retrieval systems and recommendation systems based on contextual information.